2015
DOI: 10.1021/acs.inorgchem.5b01680
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preparation, and Characterization of Zn and Cu Metallopeptides Based On Tetradentate Aminopyridine Ligands Showing Enhanced DNA Cleavage Activity

Abstract: The conjugation of redox-active complexes that can function as chemical nucleases to cationic tetrapeptides is pursued in this work in order to explore the expected synergistic effect between these two elements in DNA oxidative cleavage. Coordination complexes of biologically relevant first row metal ions, such as Zn(II) or Cu(II), containing the tetradentate ligands 1,4-dimethyl-7-(2-pyridylmethyl)-1,4,7-triazacyclononane ((Me2)PyTACN) and (2S,2S')-1,1'-bis(pyrid-2-ylmethyl)-2,2'-bipyrrolidine ((S,S')-BPBP) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Many mononuclear Cu II , Co II , Zn II and Fe II complexes which were derived from a wide range of ligands of varied skeletal structures and geometrical environments have been extensively used as catalysts for DNA cleavage . Model systems incorporating multi‐nuclear 3d metal(II) complexes and sometimes hetero‐dinuclear metal ions were also employed , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many mononuclear Cu II , Co II , Zn II and Fe II complexes which were derived from a wide range of ligands of varied skeletal structures and geometrical environments have been extensively used as catalysts for DNA cleavage . Model systems incorporating multi‐nuclear 3d metal(II) complexes and sometimes hetero‐dinuclear metal ions were also employed , .…”
Section: Introductionmentioning
confidence: 99%
“…The rate enhancement observed in these reactions and in the hydrolysis of simple phosphodiester compounds, which were used to mimic the P–O bond situation in DNA, were attributed to the formation of double Lewis structures and the synergistic effect between the two metal ions , . Inspection of literature data for the DNA cleavage under physiological conditions revealed that some mononuclear Cu II and Co II complexes could enhance the rate of DNA cleavage by a factor of 10–100 million when compared to the non‐catalyzed reaction , , , …”
Section: Introductionmentioning
confidence: 99%
“…Epoxidation of alkenes was also possible with the same catalyst mixture. Finally, copper and zinc complexes of 57 showed DNA‐cleavage activity …”
Section: Synthesis Of 22′‐dipyrrolidinesmentioning
confidence: 93%
“…Recently, it has been reported the synthesis of Zn(II) and Cu(II) metallopeptides based on PyTACN and (S,S')-BPBP tetradentate aminopyridine ligands in the context of ROS generation in cancer therapies (Figure 1d). 37 The preparation of these metallopeptides relied on the solid-phase synthesis of the corresponding metal binding peptide, subsequent cleavage from the solid support and metallation with a Zn(II) or Cu(II) salt. These two metal binding peptides were obtained following two different approaches.…”
Section: Metallopeptides: Synthetic Approachesmentioning
confidence: 99%